Sequence-function relationships of the Vitis vinifera L. terpene synthase (VviTPS) family towards understanding the grapevine flower volatilome - Smit, Jacobus Samuel (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.